2009
DOI: 10.1039/b916020e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and X-ray structural analysis of platinum and ethynyl-platinum corannulenes: supramolecular tectons

Abstract: The synthesis and characterization of two direct platinum (1 and 6a/b) and three ethynyl-platinum corannulene derivatives (2, 8 and 9), bearing 2, 4, or 5 square planar platinum centers, are presented. The structure of the bowl bearing substituents remains comparable to corannulene and the dynamic behavior of the bowl inversion as assessed by VT NMR supports a persistent bowl structure in solution. These platinum-corannulenes are well-structured tectons for the future assembly of coordination Platonic polyhedr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In 2005, Lee and Sharp [13] showed that oxidative addition of bromocorannulene to Ni(COD) 2 /2PEt 3 and Pt(PEt 3 ) 4 opens a route to -bonded organometallic corannulene derivatives. In 2009, these systems were substantially expanded by Siegel and co-workers [14] and others [15] to include reactions with multisubstituted halo-and ethynylcorannulenes.…”
Section: Buckybowls: Progress and Challenges Of Metal Binding Reactionsmentioning
confidence: 99%
“…In 2005, Lee and Sharp [13] showed that oxidative addition of bromocorannulene to Ni(COD) 2 /2PEt 3 and Pt(PEt 3 ) 4 opens a route to -bonded organometallic corannulene derivatives. In 2009, these systems were substantially expanded by Siegel and co-workers [14] and others [15] to include reactions with multisubstituted halo-and ethynylcorannulenes.…”
Section: Buckybowls: Progress and Challenges Of Metal Binding Reactionsmentioning
confidence: 99%
“…Judging from the 19 F NMR spectrum the C 1 -symmetrical (one broad signal at À52.88 and two sharp singlets at À57.90 and À60.13 ppm in a 2:1:1 ratio) asym-6 and the C 2 -symmetrical compound (two singlets in the 19 F NMR spectrum at À52.94 À55.08 ppm in a ratio of 1:1) sym-6 were unambiguously identified. Both fluoranthenes were accumulated and subjected to the ring-closing protocol, which yielded the desired corannulene only in the case of sym-6, to form 1,2,6,7-tetrakis(trifluoromethyl)corannulene (12).…”
Section: Synthesesmentioning
confidence: 99%
“…The product was obtained as a yellow-green solid 698 mg (54 %). General procedure for the synthesis of 1,2-disubstituted corannulenes (12,13): For reaction times, solvent and reagent quantities for each compound, see the Supporting Information; for the preparation of 10 and 11, see ref.…”
Section: Instrumentationmentioning
confidence: 99%
“…The properties of corannulene have been known to be modified by fusing with a variety of substituted groups with different compositions, lengths and numbers, by introducing additional five‐ and/or six‐membered rings, by forming salt‐like complexes with various metals and metal‐containing complexes and by working as a host of inclusion complexes, as explained above. Buckybowls, representing by corannulene and its derivatives, have been discussed and reviewed as possible candidates for different applications, such as molecular switches and motors for future nanoscale machinary, specifically important members in organometallics and supramolecules for chemical encapsulation and delivery of drugs and biomolecules, photoemitters of electrons, etc., as well as the precursors for the synthesis of fullerenes and redox‐acitive materials …”
Section: Discussionmentioning
confidence: 99%
“…24, 3206-3223 a host of inclusion complexes, as explained above. Buckybowls, representing by corannulene and its derivatives, have been discussed and reviewed as possible candidates for different applications, such as molecular switches and motors for future nanoscale machinary, [ 128,129 ] specifi cally important members in organometallics [130][131][132][133] and supramolecules for chemical encapsulation and delivery of drugs and biomolecules, [ 117,134,135 ] photoemitters of electrons, [ 136,137 ] etc., as well as the precursors for the synthesis of fullerenes [ 4,138,139 ] and redox-acitive materials. [ 140 ] Here, two additional possibilities for application in the fi eld of materials science and engineering have to be pointed out: corannulene and its derivatives may have certain possibilities as host materials for hydrogen and lithium storages.…”
Section: Discussionmentioning
confidence: 99%